Early, specialist vocational rehabilitation to facilitate return to work after traumatic brain injury: the FRESH feasibility RCT - Kate Radford; Chris Sutton; Tracey Sach; Jain Holmes; Caroline Watkins; Denise Forshaw; Trevor Jones; Karen Hoffman; Rory O’Connor; Ruth Tyerman; Jose Antonio Merchán-Baeza; Richard Morris; et al. (Health Technology Assessment, 2018)
Background: Up to 160,000 people incur traumatic brain injury (TBI) each year in the UK. TBI can have profound effects on many areas of human functioning, including participation in work. There is limited evidence of the clinical effectiveness and cost-effectiveness of vocational rehabilitation (VR) after injury to promote early return to work (RTW) following TBI. Objective: To assess the feasibility of a definitive, multicentre, randomised controlled trial (RCT) of the clinical effectiveness and cost-effectiveness of early, specialist VR plus usual care (UC) compared with UC alone on work retention 12 months post TBI. Design: A multicentre, feasibility, parallel-group RCT with a feasibility economic evaluation and an embedded mixed-methods process evaluation. Randomisation was by remote computer-generated allocation. Setting: Three NHS major trauma centres (MTCs) in England. Participants: Adults with TBI admitted for > 48 hours and working or studying prior to injury. Interventions: Early specialist TBI VR delivered by occupational therapists (OTs) in the community using a case co-ordination model. Main outcome measures: Self-reported RTW 12 months post randomisation, mood, functional ability, participation, work self-efficacy, quality of life and work ability. Feasibility outcomes included recruitment and retention rates. Follow-up was by postal questionnaires in two centres and face to face in one centre. Those collecting data were blind to treatment allocation. Results: Out of 102 target participants, 78 were recruited (39 randomised to each arm), representing 39% of those eligible and 5% of those screened. Approximately 2.2 patients were recruited per site per month. Of those, 56% had mild injuries, 18% had moderate injuries and 26% had severe injuries. A total of 32 out of 45 nominated carers were recruited. A total of 52 out of 78 (67%) TBI participants responded at 12 months (UC, n = 23; intervention, n = 29), completing 90% of the work questions; 21 out of 23 (91%) UC respondents and 20 out of 29 (69%) intervention participants returned to work at 12 months. Two participants disengaged from the intervention. Face-to-face follow-up was no more effective than postal follow-up. RTW was most strongly related to social participation and work self-efficacy. It is feasible to assess the cost-effectiveness of VR. Intervention was delivered as intended and valued by participants. Factors likely to affect a definitive trial include deploying experienced OTs, no clear TBI definition or TBI registers, and repatriation of more severe TBI from MTCs, affecting recruitment of those most likely to benefit/least likely to drop out. Limitations: Target recruitment was not reached, but mechanisms to achieve this in future studies were identified. Retention was lower than expected, particularly in UC, potentially biasing estimates of the 12-month RTW rate. Conclusions: This study met most feasibility objectives. The intervention was delivered with high fidelity. When objectives were not met, strategies to ensure feasibility of a full trial were identified. Future work should test two-stage recruitment and include resources to recruit from ‘spokes’. A broader measure covering work ability, self-efficacy and participation may be a more sensitive outcome. Trial registration: Current Controlled Trials ISRCTN38581822. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 22, No. 33. See the NIHR Journals Library website for further project information.